A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia - Ishak, Nurul Huda Binti Ahmad; Adam, Nur ‘Aliah Binti; Kassim, Zaleha (Zootaxa, 2018)
The marine pelagic tunicates of Family Salpidae Lahille, 1888 presence in the coastal waters of Terengganu was studied for the first time. Samples were collected from April to July 2016 using 200µm Bongo net; hauled vertically from a stationary vessel; and preserved in 5% buffered formaldehyde. A total of 4 species under this family were found, observed and identified: Thalia rhomboides (Quoy and Gaimard 1824); Thalia sibogae (van Soest 1973); Weelia cylindrica (Cuvier 1804) and Brooksia rostrata (Traustedt 1893). All species were identified as new records in Malaysian waters. The description on morphological characteristics and a key to the solitary and aggregate of the recorded species is added. The distribution was analyzed from the 18 sampling stations in theTerengganu waters including Pulau Bidong, Pulau Yu and Pulau Kapas. The collected data was then compiled with previous available global literature on the distribution and occurrence of these four species, consequently updating the biodiversity of Malaysian fauna and its worldwide biogeography distribution.